2017
DOI: 10.3892/ol.2017.7676
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase is overexpressed in thymic epithelial tumors and may serve as an independent prognostic biomarker

Abstract: Focal adhesion kinase (FAK) has long been considered to be a key regulator of growth factor receptor- and integrin-mediated signals, with pivotal roles in tumor cells through its kinase activity and scaffolding function. Increased FAK expression and activity has been observed in tumors of various origins and is often associated with a poor prognosis. However, there have been no studies on the aberrant expression of FAK in thymic epithelial tumors to date. The aim of the present study was to evaluate FAK expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…However, the drawback is that there is no comparison with the current Masaoka staging system. Literature had also reported that overexpression of focal adhesion kinase ( FAK ) protein in TETs was associated with poor prognosis and may serve as an independent prognostic biomarker for TETs [30]. Xu RH et al reported that DNA methylation sites can be used for tumor diagnosis and prognosis, which further support our current findings [31].…”
Section: Discussionsupporting
confidence: 87%
“…However, the drawback is that there is no comparison with the current Masaoka staging system. Literature had also reported that overexpression of focal adhesion kinase ( FAK ) protein in TETs was associated with poor prognosis and may serve as an independent prognostic biomarker for TETs [30]. Xu RH et al reported that DNA methylation sites can be used for tumor diagnosis and prognosis, which further support our current findings [31].…”
Section: Discussionsupporting
confidence: 87%
“…There were 34% of the genes in the ECM-receptor interaction pathway mutated repeatedly in cancer [ 31 ]. Focal adhesion kinase (FAK) is highly expressed in thymic epithelial tumors and can be used as an independent prognostic biomarker [ 32 ]. PPAR γ overexpression more than doubled insulin-stimulated thymoma viral protooncogene phosphorylation during low lipid availability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of the interaction between the thymic stroma and extracellular matrix is underscored by the overexpression of focal adhesion kinase (FAK) in thymic epithelial tumors, especially in highly aggressive subtypes like type B2 and B3 thymomas and thymic carcinomas [ 56 ].…”
Section: Hallmarks Of Cancer In Thymic Carcinomasmentioning
confidence: 99%